Marker assisted pyramiding of QTLs for heat tolerance and escape upgrades heat resilience in rice (Oryza sativa L.) - Ye, Changrong; Ishimaru, Tsutomu; Lambio, Leslie; Li, Le; Long, Yu; He, Zhizhou; Htun, Than Myint; Tang, Shunxue; Su, Zhenxi (Research Square Platform LLC, 2021)
High temperature at flowering stage of rice causes low spikelet fertility and low yield. To cope with high temperature stress brought by climate change, two strategies were proposed to develop heat-resilient rice varieties. One is to escape the high temperature by flowering early in the morning, another is to enhance tolerance to high temperature stress per se. Two promising QTLs for early morning flowering (qEMF3) and heat tolerance (qHTSF4.1) were introgressed into IR64 background, and near isogenic lines (NILs) IR64+qEMF3 (IR64EMF3) and IR64+qHTSF4.1 (IR64HT4) were developed in previous studies. In this study, a QTL pyramiding line IR64+qHTSF4.1+qEMF3 (IR64HT4EMF3) was developed by marker assisted selection of the progenies of previous NILs. The NILs were subjected to different high temperature regimes in the indoor growth chambers and different locations in the field. In the indoor growth chambers, when high temperature starts early (before 11:00 am), IR64HT4 and IR64HT4EMF3 had higher spikelet fertility than IR64EMF3; when high temperature comes later (after 11:00 am), IR64EMF3 and IR64HT4EMF3 had higher spikelet fertility than IR64HT4. The flowering pattern of the IR64HT4EMF3 was earlier than IR64HT4, but similar to IR64EMF3 in the glasshouse, field and indoor growth chambers. IR64HT4EMF3 showed higher spikelet fertility than IR64EMF3 and IR64HT4 in the field in the Philippines. Thus, combination of early morning flowering and heat tolerance QTLs is an elegant breeding strategy to cope with future extreme climate.